European Agreement concerning the International Carriage of Dangerous Goods by Inland Waterways (ADN) : including the annexed regulations, applicable as from 1 January 2011 (United Nations, 2010)
"The European Agreement concerning the International Carriage of Dangerous Goods by Inland Waterways (ADN) agreed in Geneva on 26 May 2000 under the auspices of the United Nations Economic Commission for Europe (UNECE) and the Central Commission for Navigation on the Rhine (CCNR) entered into force on 28 February 2008. The Agreement currently has fourteen Contracting Parties: Austria, Bulgaria, Croatia, France, Germany, Hungary, Luxembourg, Netherlands, Poland, Republic of Moldova, Romania, Russian Federation, Slovakia and Ukraine. Other Member States of the United Nations Economic Commission for Europe whose territory contains inland waterways, other than those forming a coastal route, may also become Contracting Parties to the Agreement by acceding to it, on condition that the inland waterways are part of the network of inland waterways of international importance as defined in the European Agreement on Main Inland Waterways of International Importance (AGN)."--Publisher's description.